Soviet childhood: homelessness and neglect of children in Central Kazakhstan during the Great Patriotic War (1941–1945) - Saktaganova, Z.G.; Abdukarimova, Zh.K.; Salnikova, A.A. (KU Publ., 2021)
The article addresses children's everyday life during the Great Patriotic War on the example of homelessness, neglect, child delinquency in Central Kazakhstan. The number of children without parental care has increased significantly compared to the pre-war period. However, there were frequent cases of neglect, crime among children living in families. The state took upon itself all the care of Soviet children and a certain transformation took place in society in relation to war orphans. Despite all the measures taken, homelessness, neglect and, as a result, juvenile delinquency were a serious problem.The issues of homelessness and neglect of children in Kazakhstan during the war years are poorly studied today. The authors for the first time designated the regional aspect of the problem of child homelessness and neglect. Documents from the Archive of the President of the Republic of Kazakhstan, the Central State Archives of the Republic of Kazakhstan, as well as the State Archives of the Karaganda region are being introduced into scientific circulation. The article presents the general picture on the issue of homelessness and neglect of children in Kazakhstan by regions, as well as the work of children's receivers of the NKVD and measures to combat these phenomena. Despite the fact that the state and society was doing colossal work with the negative consequences of the war for children, the problem remained relevant and required large material and labor costs, more thorough work in matters of upbringing, education and organization of children's leisure.
Кеңестік балалық шақ: Ұлы Отан соғысы жылдарындағы Орталық Қазақстандағы балалардың панасыздығы мен қараусыз қалуы (1941–1945 жж.)
Советское детство: беспризорность и безнадзорность детей Центрального Казахстана в годы Великой Отечественной войны (1941–1945 гг.)
Keywords: children; Soviet childhood; homelessness; neglect; juvenile delinquency; The Great Patriotic War; orphanages; Central Kazakhstan